1987
DOI: 10.1002/art.1780300603
|View full text |Cite
|
Sign up to set email alerts
|

Articular indices of joint inflammation in rheumatoid arthritis. Correlation with the acute‐phase response

Abstract: The joints of 30 rheumatoid arthritis patients were assessed by one observer for signs of inflammation. Computer analysis was then used to calculate 70 different articular indices for each patient. Pearson correlation coefficients were calculated between serum C-reactive protein levels and the articular indices. The results show that: findings in a restricted set of examined joints were equivalent to those in a more complete set; the simultaneous presence of joint tenderness and swelling yielded higher correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
61
2
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(69 citation statements)
references
References 6 publications
5
61
2
1
Order By: Relevance
“…Those patients with a higher ESR at baseline developed more erosions. Other studies have also identified elevated ESR as being predictive of radiographic progression (24)(25)(26). We were unable to correlate other baseline variables, including duration of arthritis, presence of rheumatoid factor, or clinical variables including the number of painful or swollen joints, with a worsening of the erosion score.…”
Section: Discussionmentioning
confidence: 98%
“…Those patients with a higher ESR at baseline developed more erosions. Other studies have also identified elevated ESR as being predictive of radiographic progression (24)(25)(26). We were unable to correlate other baseline variables, including duration of arthritis, presence of rheumatoid factor, or clinical variables including the number of painful or swollen joints, with a worsening of the erosion score.…”
Section: Discussionmentioning
confidence: 98%
“…In spite of overall general consensus, one major unresolved issue (5)(6)(7) relates to the question of whether extended or reduced joint counts would be superior in clinical studies. Satisfactory correlation with extended joint counts has been previously shown for reduced joint counts (8)(9)(10)(11)(12). A 28-joint count has been developed as a simplified joint score and as a compromise between comprehensiveness and feasibility (8).…”
mentioning
confidence: 76%
“…The observer may record tenderness, swelling, pain on motion, deformity, and limitation of motion quantitatively or as normal/abnormal (1). In clinical trials, emphasis is placed on tenderness and swelling, findings which represent inflammation and are amenable to short-term improvement or decline (2). Pain on motion is highly correlated with tenderness (3) and has been used as a surrogate measure for tenderness in joints in which tenderness is difficult to assess, such as the shoulder, hips, and cervical spine (4).…”
mentioning
confidence: 99%